Aspect of Movement in Art Performance of Tupai Janjang as A Cultural Heritage of The People of Palembayan - Gusnia; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study was to explain and describe the Existence of Motion in the Squirrel Janjang Art Performance as a Cultural Heritage of the Palebayan Community This research uses a qualitative research type with a descriptive method. This summary provides a brief overview of the research methods, research objects, instruments, data types, data collection techniques, and data analysis techniques used in research on Janjang Tupai Art as a Cultural Heritage of the Palebayan Market Community which needs to be revitalized. From the story of Tupai Janjang, Tuak Ampek worked on it to become an art called Janjang Squirrel Art. Tupai Janjang art is a form of storytelling tradition in which a storyteller plays all the characters in the story while moving and singing. This performance is unique from Minangkabau traditional art, because there is no other form of performance where only one storyteller plays all the characters. Tuak Ampek took this story as a script, then turned it into an art called the Janjang Squirrel Art. In the Tupai Janjang art, one person plays all the characters in the story while moving and singing, whereas in randai, each character is played by a different actor. d. However, in its current form, two or three actors can take turns bringing this feeling to life with movement and singing that fits the story. The movement in the Tupai Janjang Art performance is based on the traditional movement of silat flowers called balabek. The revitalization efforts carried out by Osra Hayadi include data collection and the involvement of new generations in this art. The Existence of Motion in Tupai Janjang Art In performing the Tupai Janjang Art, there are many uses of traditional movements. In Seni Tupai Janjang, the actor will move according to the content of the story he is singing. In the Tupai Janjang Art performance, only accompanied by saluang, then the actors will sing while moving.